Self-hypnosis for dummies - Bryant, Michael, 1955- (--For dummies., 2010)
A hands-on guide to achieving your goals using hypnosis. Whether you want to lose weight, overcome anxiety or phobias, cure insomnia, stop smoking, or simply stop biting your nails, this guide has it covered! The reassuring and straight-talking information will help you harness the power of your mind and re-train your subconscious to think in more healthy and constructive ways, and to overcome specific issues, such as anxiety and paranoia, and break bad habits, such as smoking. The easy-to-follow style will guide you through every step of the process, empowering you to take control and start making changes right away.